En villégiature à la Cité : les collections de la Cité de l’architecture et du patrimoine - Corinne Bélier (In Situ)
The Cité de l’architecture et du patrimoine holds a great number of archives and collections related to the development of vacation places. This paper will present a history of these collections, emphasizing their weaknesses and strengths. Since its creation, the Institut français d’architecture has contributed to a better recognition of the architectural heritage of seaside and thermal resorts, through multiple exhibitions and publications and through the collecting of architectural archives. The first archives were devoted to the architecture of the Belle Époque and of the interwar period; then came the large archive of the postwar architecture agencies. The new seaside and mountain resorts corresponded to the development of mass tourism. They have been chosen, for their exemplarity, to be shown in the permanent exhibition of the museum (musée des Monuments français).